A comparison of different recombination operators for the 2-dimensional strip packing problem - Salto, Carolina (2006)
In this paper, the three-stage two-dimensional rectangular strip packing problem is tackled using genetic algorithms. A new problem dependent recombination operator, called best inherited levels recombination (BIL), is introduced. A comparison of its performance is carried out with respect to four classical recombination operators. A complete study of the influence of the recombination operators on the genetic search, including the trade-off between exploration and exploitation in the search process, is presented. The results show that the use of our specialized BIL recombination outperforms the others more generic on all problem instances for all the metrics tested